2018
DOI: 10.1002/ente.201800238
|View full text |Cite
|
Sign up to set email alerts
|

Phosphotungstic Acid Regulated Chemical Bath Deposition of Sb2S3 for High‐Efficiency Planar Heterojunction Solar Cell

Abstract: Chemical bath deposition is a convenient method for preparing Sb2S3 film which is considered as a promising photovoltaic material. However, impurity phases such as Sb2O3, SbOCl, Sb2(SO4)3 and Sb(OH)3 are inevitably generated in this solution process. Herein, we demonstrate that phosphotungstic acid in the precursor solution is able to suppress the formation of oxide and oxyhalide by‐products, leading to considerably optimized composition and crystallinity for solar cell applications. With this method, a remark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Similarly, Zhang et al found that phosphotungstic acid (PW) additive was an efficient method to suppress the formation of oxide impurities (such as Sb 2 O 3 and Sb 2 (SO 4 ) 3 ) in the Sb 2 S 3 film growth process, leading to considerably optimized surface impurities defects and film crystallinity for Sb 2 S 3 solar cells. [160] The surface of Sb 2 Se 3 films may be covered by certain amount of Sb 2 O 3 or elemental Se, which will act as the charge traps, resulting in a high back contact resistance and thereby low FF (50%). Sb 2 O 3 and elemental Se can be removed from the Sb 2 Se 3 back surface by (NH 4 ) 2 S etching.…”
Section: Defect Passivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Zhang et al found that phosphotungstic acid (PW) additive was an efficient method to suppress the formation of oxide impurities (such as Sb 2 O 3 and Sb 2 (SO 4 ) 3 ) in the Sb 2 S 3 film growth process, leading to considerably optimized surface impurities defects and film crystallinity for Sb 2 S 3 solar cells. [160] The surface of Sb 2 Se 3 films may be covered by certain amount of Sb 2 O 3 or elemental Se, which will act as the charge traps, resulting in a high back contact resistance and thereby low FF (50%). Sb 2 O 3 and elemental Se can be removed from the Sb 2 Se 3 back surface by (NH 4 ) 2 S etching.…”
Section: Defect Passivationmentioning
confidence: 99%
“…found that phosphotungstic acid (PW) additive was an efficient method to suppress the formation of oxide impurities (such as Sb 2 O 3 and Sb 2 (SO 4 ) 3 ) in the Sb 2 S 3 film growth process, leading to considerably optimized surface impurities defects and film crystallinity for Sb 2 S 3 solar cells. [ 160 ]…”
Section: Defect Passivationmentioning
confidence: 99%
“…The electron transport layer (ETL) and hole transport material (HTMs) ferry the electrons and holes generated in the absorber to the contacts, respectively. 3,5,[22][23][24][25][26] Indium tin oxide (ITO) and uorine doped tin oxide (FTO) are commonly used TCOs. 22,23,27 For HTMs, several organic and inorganic materials are explored.…”
Section: Introductionmentioning
confidence: 99%
“…27,29 More importantly, they need to be transparent in the visible spectral region when used in semitransparent solar cells and should be cost-effective. The most popular HTMs explored to date for Sb 2 S 3 solar cells are the organic-based P3HT (poly(3-hexylthiophene)), 3,5,22,27 spiro-OMeTAD (2,2 0 ,7,7 0 -tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9 0 -spirobi-uorene), 24,25 PEDOT:PSS (poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonate)) 23 and PCPDTBT (poly [2,6-(4,4- 30 Among inorganic materials, NiO x , 31 V 2 O 5 32 and CuSCN:KSCN 6 have been reported as HTMs. For instance, Kim et al have fabricated planar Sb 2 S 3 solar cells with spin coated PEDOT:PSS as the HTM wherein Sb 2 S 3 is deposited using CBD, and have obtained a PCE of 5.8%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation